Optimization of a 12.5 GHz Microstrip Antenna Array Using Taguchi's Method - M. Spasos; R. Nilavalan; K. Tsiakmakis; N. Charalampidis; S. W. Cheung (International Journal of Antennas and Propagation)
This paper presents Taguchi's optimization method implemented in the design of a single feed (without any matching network) 5×5 microstrip antenna array operating around 12.5 GHz. The proposed optimization method is statistical and is widely used for quality assurance in many fields such as mechanical and chemical production, consumer electronics, services; however it has been underused in the field of electromagnetics. It allows optimization of multiparameter, multitarget complex designs in a very short time in conjunction with advanced simulation tools. The proposed antenna has been fully evaluated under Taghuchi's and PSO's optimization methods, and the experimental results show total Gain of 15 dB, and good matching with S11 better than −20 dB, in the frequency range 12.3 to 12.8 GHz.